Respuesta :

ItzTds

Now we have to,

find the required value of x.

Let's begin,

→ 3x-2 = 2(x-5)

→ 3x-2 = 2x-10

→ 3x-2x = -10+2

→ x = -8

Hence, value of x is -8.

Answer:

x = -8

Step-by-step explanation:

3x - 2 = 2 ( x + 5

Solve for x.

Let's solve,

3x - 2 = 2 ( x + 5 )

Step 1:- Distribute 2.

3x - 2 = 2 × x + 2 × 5

3x - 2 = 2x - 10

Step 2 :- Move constant to the right-hand and change their sign.

3x = 2x - 10 + 2

Step 3:- Add -10 and 2.

3x = 2x - 8

Step 4 :- Move variable to the left-hand side and change their sign.

3x - 2x = -8

Step 5 :- Subtract 2x from 2x.

x = -8

Hence, value of x = -8.